Area of a triangle having sides π‘Ž, 𝑏, 𝑐 units long is equal to

1

βˆšπ‘ (𝑠 βˆ’ π‘Ž)(𝑠 βˆ’ 𝑏)(𝑠 βˆ’ 𝑐), where 𝑠 = (π‘Ž + 𝑏 + 𝑐).
2 𝑐 π‘Ž

β„Ž π‘₯ 𝑏

βˆ’π‘₯ 𝑏

Proof
1 π‘Ž 𝑏 𝑐

1

First of all, note that 𝑠 βˆ’ π‘Ž = 2 (π‘Ž + 𝑏 + 𝑐) βˆ’ π‘Ž = 2 + 2 + 2 βˆ’ π‘Ž = 2 (𝑏 + 𝑐 βˆ’ π‘Ž).
1

1

Similarly 𝑠 βˆ’ 𝑏 = 2 (π‘Ž + 𝑐 βˆ’ 𝑏) and 𝑠 βˆ’ 𝑐 = 2 (π‘Ž + 𝑏 βˆ’ 𝑐).
Now consider the height of the triangle β„Ž. We can apply Pythagoras’ Theorem twice: π‘Ž
2 = β„Ž2 + π‘₯ 2 , 𝑐

2 = β„Ž2 + (𝑏 βˆ’ π‘₯)2

Hence
β„Ž2 = π‘Ž2 βˆ’ π‘₯ 2 = 𝑐 2 βˆ’ (𝑏 βˆ’ π‘₯)2 π‘Ž
2 βˆ’ π‘₯ 2 = 𝑐 2 βˆ’ (𝑏 2 βˆ’ 2𝑏π‘₯ + π‘₯ 2 ) π‘Ž
2 βˆ’ π‘₯ 2 = 𝑐 2 βˆ’ 𝑏 2 + 2𝑏π‘₯ βˆ’ π‘₯ 2 π‘Ž
2 + 𝑏 2 βˆ’ 𝑐 2 = 2𝑏π‘₯ π‘Ž
2 + 𝑏 2 βˆ’ 𝑐 2 π‘₯
=
2𝑏
Thus
2 π‘Ž

2

β„Ž2
β„Ž2
β„Ž2
β„Ž2 π‘Ž

2 + 𝑏 2 βˆ’ 𝑐 2
=β„Ž +(
)
2𝑏
(π‘Ž2 + 𝑏 2 βˆ’ 𝑐 2 )2
= π‘Ž2 βˆ’
4𝑏 2
2 2
4π‘Ž 𝑏 βˆ’ (π‘Ž2 + 𝑏 2 βˆ’ 𝑐 2 )2
=
4𝑏2
2
(2π‘Žπ‘) βˆ’ (π‘Ž2 + 𝑏 2 βˆ’ 𝑐 2 )2
=
4𝑏 2
2
(2π‘Žπ‘ + (π‘Ž + 𝑏 2 βˆ’ 𝑐 2 ))(2π‘Žπ‘ βˆ’ (π‘Ž2 + 𝑏 2 βˆ’ 𝑐 2 ))
=
4𝑏 2
2

(using difference of two squares)
β„Ž2 =

((π‘Ž2 + 2π‘Žπ‘ + 𝑏 2 ) βˆ’ 𝑐 2 )(𝑐 2 βˆ’ (π‘Ž2 βˆ’ 2π‘Žπ‘ + 𝑏 2 ))
4𝑏 2

((π‘Ž + 𝑏)2 βˆ’ 𝑐 2 )(𝑐 2 βˆ’ (π‘Ž βˆ’ 𝑏)2 )
4𝑏 2
((π‘Ž + 𝑏) + 𝑐)((π‘Ž + 𝑏) βˆ’ 𝑐)(𝑐 + (π‘Ž βˆ’ 𝑏))(𝑐 βˆ’ (π‘Ž βˆ’ 𝑏))
β„Ž2 =
4𝑏 2
β„Ž2 =

(using difference of two squares twice)
(π‘Ž + 𝑏 + 𝑐)(π‘Ž + 𝑏 βˆ’ 𝑐)(π‘Ž + 𝑐 βˆ’ 𝑏)(𝑏 + 𝑐 βˆ’ π‘Ž)
4𝑏 2
(2𝑠)(2(𝑠
βˆ’ 𝑐))(2(𝑠 βˆ’ 𝑏))(2(𝑠 βˆ’ π‘Ž))
β„Ž2 =
4𝑏 2
β„Ž2 =

(using previous argument)
4 𝑠
(𝑠 βˆ’ π‘Ž)(𝑠 βˆ’ 𝑏)(𝑠 βˆ’ 𝑐) 𝑏
2
2
β„Ž = βˆšπ‘ (𝑠 βˆ’ π‘Ž)(𝑠 βˆ’ 𝑏)(𝑠 βˆ’ 𝑐) 𝑏

β„Ž2 =

Hence we have
1 𝑏
2
Area of Triangle = π‘β„Ž = ( βˆšπ‘ (𝑠 βˆ’ π‘Ž)(𝑠 βˆ’ 𝑏)(𝑠 βˆ’ 𝑐)) = βˆšπ‘ (𝑠 βˆ’ π‘Ž)(𝑠 βˆ’ 𝑏)(𝑠 βˆ’ 𝑐)
2
2 𝑏
as required.

Sign up to vote on this title
UsefulNot useful